2019
DOI: 10.1002/macp.201900416
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Ring‐Opening Alternating Copolymerization of Epoxides and Cyclic Anhydrides Mediated by a Ternary Phosphazene Base and Carboxylic Acids

Abstract: Organocatalytic, metal‐free ring‐opening alternating copolymerization (ROAP) of epoxides and cyclic anhydrides to produce polyesters with well‐defined alternating structure remains a challenge despite several organocatalysts having been reported. Herein, the ROAP of cyclohexene oxide (CHO) with phthalic anhydride (PA) using a series of carboxylic acids as initiator in the presence of an organic cyclic trimetric phosphazene base (CTPB) as catalyst is reported. The molar ratio of CTPB to carboxylic acid is prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…DOSY NMR analysis confirmed that the copolymers isolated were one polymeric species and matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) analysis provided evidence that there were ester and ether linkages present. However, the systems were complicated and a range of potential end groups were proposed relating to the auxiliary ligands (X = OAc or Cl) or hydrolysis and chloro-functionalization indicative of chain-transfer reactions occurring upon termination and isolating the polymers with the acidified MeOH/HCl work-up (see the Supporting Information, Figures S37–S42), or possibly cyclohexane/cyclohexene from potential Meerwein–Ponndorf–Verley reduction/Oppenauer oxidation side reactions. ,,, IR analysis was consistent with the literature (Figures S23 and S24). …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…DOSY NMR analysis confirmed that the copolymers isolated were one polymeric species and matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) analysis provided evidence that there were ester and ether linkages present. However, the systems were complicated and a range of potential end groups were proposed relating to the auxiliary ligands (X = OAc or Cl) or hydrolysis and chloro-functionalization indicative of chain-transfer reactions occurring upon termination and isolating the polymers with the acidified MeOH/HCl work-up (see the Supporting Information, Figures S37–S42), or possibly cyclohexane/cyclohexene from potential Meerwein–Ponndorf–Verley reduction/Oppenauer oxidation side reactions. ,,, IR analysis was consistent with the literature (Figures S23 and S24). …”
Section: Resultssupporting
confidence: 69%
“…However, the systems were complicated and a range of potential end groups were proposed relating to the auxiliary ligands (X = OAc or Cl) or hydrolysis and chlorofunctionalization indicative of chain-transfer reactions occurring upon termination and isolating the polymers with the acidified MeOH/HCl work-up (see the Supporting Information, Figures S37−S42), or possibly cyclohexane/cyclohexene from potential Meerwein−Ponndorf−Verley reduction/Oppenauer oxidation side reactions. 35,52,62,69 IR analysis was consistent with the literature S23 and S24). 33 ROCOP of Cyclohexene Oxide and PA in Neat Cyclohexene Oxide.…”
Section: ■ Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the same vein, the presence of alkoxide species in the reaction mixture, due to the use of strong bases as initiators, may lead to intra-or intermolecular transesterifications which are detrimental to polymerization control and thus materials properties. The homopolymerization of epoxides, attributed to excessive activation by strong Lewis acids 48 or the use of strong bases, 56 is also an obstacle to a well-behaved alternating ROCOP of anhydrides and epoxides. The comparison of the efficiency of the organocatalysts used in the Fischer-Inoue-Coates reaction is not straightforward given the diversity of the monomers employed.…”
Section: Discussionmentioning
confidence: 99%
“…Organometallics with a trivalent metal center (such as Co, Cr, and Al) have prevailed in ROAC for a long time. However, the toxic metal residuals played a detrimental role in the final product performance, to some extent, limiting their potential applications in microelectronics, food packing, and biomedical devices. To address the concern of metal contaminants and realize a relatively green synthetic process, metal-free catalysis has been developed in recent years, including quaternary onium salts, , phosphazenes, and other nucleophilic bases. , Most of the organic catalysts showed low catalytic activity even at a high temperature and limited monomer adaptability. For example, succinic anhydride (SA) and maleic anhydride (MA), both of which are recognized as top value added chemicals from biomass and produced in a large scale, can not be copolymerized smoothly with epoxides by most organocatalysts because of the deprotonation of the active α-proton.…”
Section: Introductionmentioning
confidence: 99%